Tata Ruang Gedung Untuk Pernikahan Menggunakan Marker Augmented Reality - Shafa'atul Aliyah; Anang Kukuh Adisusilo; Beny YV Nasution (Melek IT : Information Technology Journal, 2016)
Marriage is a sacred thing which must be done by every human with their respective spouses to be used as a binder a good relationship in terms of religion and state law. Marriage is a very complicated planning stages. With the new technology called augmented reality it is difficult to penataan room can be a little overcome by using this application. Augmented Reality is a technology that combines virtual objects are two-dimensional and three-dimensional games into a real environment and projecting a three-dimensional virtual objects in real time. The method used in this simulation using augmented reality marker. The results of this application is that it can adjust the location of the 3D objects of equipment required can be in accordance with the desired adjustment of 3D objects that one with 3D objects that others can be positioned as desired that the marker can be read by the camera with a radius of at least 2 meters and radius a maximum of 6 meters in the form of a 3D object from the altar. Then detected by a camera with a radius of at least 1 meters and a maximum radius of 4 meters in the form of a 3D object from a red flower, blue flowers, red companion seat and companion seat wood. While markers that can be caught on camera with a radius of at least 2 meters and a maximum radius of 5 meters in the form of a 3D object main seat red and blue primary seat and the camera can detect a marker and to produce a good 3D image object.